The International famous prize 6-horse team of Wilson & Co., Meat Packers posed in front of the Wilson World's Fair Exhibit Building, Northerly Island in the Heart of the Midway (Curt Teich & Co., Inc.)
Visit and Dine aat the Wilson Exhibit Building or any of the Wilson Food Stands on the Fair Grounds. See the team on Exhibition at The Wings of a Century, and at our stables nearby this concession of historical pageantry.